Plate girders with corrugated webs - Pasternak, Hartmut; Kubieniec, Gabriel (Journal of Civil Engineering and Management, 2010)
Especially for the main frames of single‐storey steel buildings the use of corrugated web beams, mainly with sinusoidal corrugation, has been increased very much during the last years. Due to the thin web of 1,5 mm to 3 mm corrugated web beams afford a significant weight reduction compared with hot rolled profiles or welded I‐sections. Buckling failure of the web is prevented by the corrugation. The buckling resistance of presently used sinusoidal corrugated webs is comparable with plane webs of 12 mm thickness or more. Due to improvements of the automatic fabrication process corrugated webs up to 6 mm thickness became possible. Therefore the field of application of this beam type has been extended considerable. Even short span bridges are possible now. The dimensioning of corrugated web beams is ruled by the EN 1993–1‐5 Annex D ‐ it covers only web thicknesses up to 3 mm. In the last years many tests and finite element simulations have been carried out. Regarding this background, these EN rules will be discussed and extended. Furthermore, additional proposals for patch loading and lateral‐torsional buckling of girders with sinussoidal webs will be given. First Published Online: 24 Jun 2011